Evalution Of The Phytochemical Constituents Of Acmella Calva (DC.) R. K. Jansen - P. SHANTHI; P. AMUDHA (International Journal of Pharma and Bio Sciences, 2010)
Acmella calva (DC.) R.K.Jansen., commonly known as toothache plant was analyzed for their chemical composition and minerals. The various extracts of the plant parts (leaves, inflorescence and whole plant) possessed the presence of active phytochemical constituents such as alkaloids, glycosides, flavanoids, reducing sugar, tannins, anthraquinone, saponins and cardiac glycosides. The amount of total soluble protein (0.78±0.09 mg/g) and the total free amino acids (14.95±1.00 mg/g) was remarkably high in the inflorescence. In the whole plant, the carbohydrates content was (6.66±0.35 mg/g) estimated in high quantity. The secondary plant products such as phenols (6.14±0.46 mg/g) and tannins (2.63±0.06 mg/g) were found maximum in the leaves. The herb is a good source of minerals. The maximum amount of nitrogen (0.24±0.15 mg/g) and phosphorus (0.06±0.07 mg/g) was obtained in the inflorescence and the iron (2.67±0.05 mg/g) content was recorded high in the leaves.